Hydrochemistry of a Tropical harbor: Influence of Industrial and Municipal inputs - Balogun Kayode James; Ladigbolu Ismail Adejare; Olaji Ebenezer Dayo (Journal of Applied Sciences and Environmental Management)
In recent times, pollution hazards of coastal waters have increased due to human activities including sand mining and dredging, industrial effluent discharges, indiscriminate dumping of sewage and domestic waste, use of detergents and heavy metals. A study was carried out to assess the extent of pollution caused by industrial and municipal discharges in the Lagos Harbour. Composite samples were collected monthly from the Harbour at seven locations from June to November, 2009 (covering parts of the rainy and dry seasons) and analyzed for some pollution parameters and trace elements [(Temperature, pH, Conductivity, Turbidity, Salinity, Total Dissolved Solids, Dissolved Oxygen, Alkalinity, Organic matters (BOD, COD), Nutrients (NO3, PO4 and SiO4) and Heavy metals (Cr, Pb, Cd, Cu and Fe)]. Surface water of the Harbour was characterized by fairy constant temperature with a range of ( 25.67 – 28.33oC), alkaline pH (7.70 – 8.42mg/l), brackish salinity (7.00 – 22.47PSU), BOD5 and COD values of (0.80 – 3.33mg/l) and (6.10 – 11.30mg/l) respectively, total dissolved solids(6.00 – 19.00mg/l), dissolved oxygen content (4.13 – 7.60mg/l) which fell below FEPA limit of 10mg/l, alkalinity (8.00 – 15.33mg/l), low Nitrate value (0.08 – 0.12mg/l), moderately high Phosphate (0.57 – 1.60mg/l), high Silicate values (1.27 – 9.23mg/l), moderate concentration of heavy metals salts such as Cr (0.03 – 0.60mg/l), Pb (0.22 – 0.61mg/l), Cd (nd – 0.02mg/l, Fe (0.67 – 1.41mg/l) and high Cu values (4.53 – 5.55mg/l). Correlation between Salinity and heavy metals measured in this study were negative except Iron. Considering the values recorded for the pollution indicators, the harbor appears to be organically polluted. The temporal variability in some of these parameters could be attributed to influx of freshwater during the rainy season. @JASEM